SCAI expert consensus update on best practices in the cardiac catheterization laboratory: This statement was endorsed by the American College of Cardiology (ACC), the American Heart Association (AHA), and the Heart Rhythm Society (HRS) in April 2021. Issue 2 (19th May 2021) - Naidu, Srihari S.; Abbott, J. Dawn; Bagai, Jayant; Blankenship, James; Garcia, Santiago; Iqbal, Sohah N.; Kaul, Prashant; Khuddus, Matheen A.; Kirkwood, Lorrena; Manoukian, Steven V.; Patel, Manesh R.; Skelding, Kimberly; et al.
Abstract: The current document commissioned by the Society for Cardiovascular Angiography and Interventions (SCAI) and endorsed by the American College of Cardiology, the American Heart Association, and Heart Rhythm Society represents a comprehensive update to the 2012 and 2016 consensus documents on patient‐centered best practices in the cardiac catheterization laboratory. Comprising updates to staffing and credentialing, as well as evidence‐based updates to the pre‐, intra‐, and post‐procedural logistics, clinical standards and patient flow, the document also includes an expanded section on CCL governance, administration, and approach to quality metrics. This update also acknowledges the collaboration with various specialties, including discussion of the heart team approach to management, and working with electrophysiology colleagues in particular. It is hoped that this document will be utilized by hospitals, health systems, as well as regulatory bodies involved in assuring and maintaining quality, safety, efficiency, and cost‐effectiveness of patient throughput in this high volume area.